EFFECT OF SOCIAL SUPPORT ON QUALITY OF LIFE AMONG ORTHOPEDICALLY DISABLED STUDENTS AND TYPICAL STUDENTS - Sultan, Bukhtawar; Malik, Najma Iqbal; Atta, Mohsin (Journal of Postgraduate Medical Institute, 2016)
Objective: To examine the impact of social support on quality of life among orthopedically disabled and typical students. Methodology: Urdu version of WHO Quality of Life Scale (Brief version) (Khan, Akhter, Ayub, Alam, & Laghari, 2003) and Multidimensional Scale of Perceived Social Support (Batool, 2012) were administered in order to get the required information. Study involved 75 orthopedically disabled students (35 females, 40 males) and 150 typical students (73 females, 77 males) with the age range of 12 to 35 (M = 17.11± 4.71), who were selected through purposive convenient sampling. Pearson correlation analysis revealed significant positive correlation among all variables for all categories of sample. Results: Linear regression analysis revealed that social support positively predicts quality of life (physical functioning, psychological functioning, social dimensions and environment) for both categories of sample. Conclusion: As compared to orthopedically disabled students, typical students tend to enjoy more social support which results in enhancing their quality of life and its pertaining components.